IN VITRO MANAGEMENT OF CURVULARIA LEAF SPOT OF MAIZE USING BOTANICALS, ESSENTIAL OILS AND BIO-CONTROL AGENTS - BISHT, SUNAINA; KUMAR, PRADEEP; A. SRINIVASANRAGHAVAN; PUROHIT, JYOTIKA (The Bioscan, 2013)
Different plant extracts, essential oils and different strains of Trichoderma harzianum were evaluated in vitro against Curvularia lunata. Amongst the plant extracts, Lantana was highly effective @ 15 per cent (86.76 inhibition %) and 20 per cent (89.49 inhibition %) followed by Morphankhi @ 5 per cent (83.53 %) and 10 per cent (85.88 %) respectively. Among the essential oils, complete inhibition was recorded in Citronella oil at all 3 concentrations (2µL, 4µL and 8) and Peppermint oil at 4µL and 8 µL concentrations and least inhibition was observed in Palmaroza (65 %) at 2µL. Whereas, among different strains of Trichoderma harzianum, Th-13 shown maximum mycelial growth inhibition (83.82 %) followed by Th-9 (80.29 %) and Th-3(79.12 %).